Vestibular Migraine Therapy: Update and Recent Literature Review - Laura Zanandrea; Bruno Colombo; Massimo Filippi (Audiology Research, 2023)
Vestibular migraine (VM) is a neurological condition that causes vertigo and headache. It is considered the most common cause of episodic vertigo. However, specific treatments are missing, and medications currently used in VM are borrowed from migraine therapy. A comprehensive practical review of the literature assessing the evidence for abortive and preventive interventions in adults with VM was published in 2022, providing practical recommendations about VM treatment. The aim of our paper is to provide an updated overview of the current state of the art of VM treatment, illustrating new evidence available in this field. Along with traditional pharmacological preventive therapies, medications targeting the CGRP pathways have recently been investigated in terms of treatment effect in VM patients, with encouraging results. Also, there is new evidence of the efficacy of non-pharmacological interventions. However, the overall evidence base for VM treatment remains sparse.